Mechanisms of copper metabolism and cuproptosis: implications for liver diseases - Chen, Haoran; Li, Dongxuan; Zhang, Huimin; Zhang, Meiqi; Lin, Yumeng; He, Haibei; Liu, Aijun; Shen, Shiming; Wang, Yi; Han, Zhongyu (Frontiers in Immunology, 2025)
Copper is an essential trace element in the human body, involved in various biological processes, including cell metabolism, nerve development, and immune function. Its homeostasis is vital for maintaining normal cellular functions, and disruptions in copper homeostasis can lead to a wide range of diseases. Cuproptosis is a copper ion–dependent form of programmed cell death that leads to abnormal oligomerization of lipoylated proteins and dysfunction of iron-sulfur cluster proteins in the mitochondrial tricarboxylic acid (TCA) cycle, thereby triggering intracellular oxidative stress and proteotoxic stress. In this review, we have delved into the mechanisms of copper metabolism and cuproptosis, as well as their roles in several liver diseases, including Wilson disease (WD), alcoholic liver disease (ALD), non-alcoholic fatty liver disease (NAFLD), acute liver injury (ALI), and hepatocellular carcinoma (HCC), as well as their therapeutic potential.